1998
DOI: 10.1128/jcm.36.3.830-832.1998
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Evaluation of Antimicrobial Resistance in Community-Acquired Enterococci

Abstract: Fecal samples from 200 consecutive patients admitted to a community hospital yielded 107 enterococci. High-level gentamicin resistance occurred in 10 (14%) of the Enterococcus faecalisisolates. Ampicillin resistance occurred in two (3%) of the E. faecalis isolates and six (23%) of the Enterococcus faecium isolates. There were no vancomycin-resistant enterococci. Risk factors for enterococci with high-level aminoglycoside (gentamicin) or ampicillin resistance included prior hospitalization and previous antibiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
2
1

Year Published

1999
1999
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 29 publications
1
28
2
1
Order By: Relevance
“…On the other hand, other studies have reported high prevalence rates compatible with our own: 17% in a recent French study (17), 12% in a German study (23), and 28% in a Belgian study (36). In the United States little is known about the presence of VRE in the community at large or the environment, but the limited available data are in contrast to the European data, since VRE appear to be absent or very rare in healthy people outside hospitals and in the environment (8,15,26,34).…”
Section: Discussionsupporting
confidence: 81%
“…On the other hand, other studies have reported high prevalence rates compatible with our own: 17% in a recent French study (17), 12% in a German study (23), and 28% in a Belgian study (36). In the United States little is known about the presence of VRE in the community at large or the environment, but the limited available data are in contrast to the European data, since VRE appear to be absent or very rare in healthy people outside hospitals and in the environment (8,15,26,34).…”
Section: Discussionsupporting
confidence: 81%
“…It is not clear how GRE were introduced into US hospitals. In contrast to Europe, no community GRE reservoir has been detected [63,86,142]. However, these studies have been limited in population size, and the direct plating technique used is less sensitive than selective enrichment broth [89,90].…”
Section: The Us Situation: Vancomycin As a Human Feed Additivementioning
confidence: 99%
“…Glycopeptide-resistant enterococci (GRE) were first noted in Europe in 1986 (22,38) and were subsequently noted in the United States in 1987 (34). These GRE have rapidly emerged as major nosocomial pathogens throughout the United States (23); however, until now they have not been detected in the community or in livestock (9,35,37,43). In Europe, GRE are widely distributed in the community (12), in farm and pet animals (1,11), and on raw meat and meat products (5,6,41), although their prevalence in hospitals remains very low (39).…”
mentioning
confidence: 99%